Pendidikan Gizi Melalui Permainan Wayang terhadap Peningkatan Konsumsi Sayur dan Buah - Desi Desi; Bella Mesyamtia; Martinus Ginting (Poltekkes Kemenkes Pontianak, 2018)
Abstract: Nutrition Education Through Puppet Game To Increase Consumption Of Vegetables And Fruits In Children Kindergarten.The consumption of vegetables and fruit is one indicator of nutritional balance. The statistical data show there are 60.44% of Indonesia that are less consuming vegetables and fruit. Fiber on vegetable and fruit are very useful for the body. Efforts to improve nutritional knowledge can preserve out through media which are suitable for children, that are attractive and easy to understand such as puppet and ladders game. This research aims to analyze the influence of the nutritional education through the game puppet to increase vegetable and fruit consumption for kindergarten children (TK). This is a pre-research experiment. One group pre-post test. Data analysis in this study uses the sample of this research is the Mina Muda kindergarten children from Kabupaten Kubu Raya that accounted 33 people in accordance with population. The technique of data collection from the questionnaire is based on the direct interviews, it aims to investigate the difference in vegetable consumption on kindergarten children before nutrition education is 5,64 while after nutrition is increase to 10,85. Whereas for fruit consumption for kindergarten children before education is 5,18 whereas after education is significantly increase to 15,00. The result revealed that there is an increment of vegetable and fruit consumption after nutrition education through puppet game (p =0,000) it concludes that nutritional education through puppet gameplay on an important role to increase the consumption of fruit and vegetables for kindergarten childrenAbstrak: Pendidikan Gizi Melalui Permainan Wayang Terhadap Peningkatan Konsumsi Sayur Dan Buah. Konsumsi sayur dan buah yang cukup merupakan salah satu indikator gizi seimbang. Masyarakat Indonesia (60,44%) kurang mengkonsumsi sayur dan buah. Kandungan serat pada sayur dan buah sangat berguna bagi tubuh. Upaya untuk meningkatkan pengetahuan gizi dapat dilakukakan dengan media yang tepat, menarik, dan mudah dipahami bagi anak diantaranya permainan wayang. Penelitian ini bertujuan mengetahui pengaruh pendidikan gizi melalui permainan wayang untuk meningkatkan konsumsi sayur dan buah pada anak taman kanak-kanak (TK). Penelitian ini merupakan pre-eksperimen. one group pre-post test. Analisis data pada penelitian ini menggunakan uji Paired Sample T-test. Subjek penelitian ini adalah anak taman kanak-kanak Mina Muda Kabupaten Kubu Raya berjumlah 33 sesuai dengan total populasi. Teknik pengumpulan pengisian kuesioner dipilih dengan wawancara langsung, untuk melihat perbedaan konsumsi sayur dan buah. Rata-rata konsumsi sayur pada anak taman kanak-kanan sebelum pendidikan gizi 4,64 sesudah pendidikan gizi 10,85. Konsumsi buah pada anak taman kanak-kanak sebelum pendidikan 5,18 sesudah pendidikan mengalami kenaikan menjadi 15,00. Menyatakan bahwa ada perbedaan konsumsi sayur sesudah pendidikan gizi melalui permainan wayang (p=0,000). Terdapat pengaruh signifikan konsumsi buah melalui permaianan wayang f (p=0,000). Pendidikan gizi melalui permaianan wayang mampu meningkatkan konsumsi sayur dan buah pada anak taman kanak-kanak.